1988
DOI: 10.1007/bf02028274
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cysteinyl-leukotriene production by azelastine and its biological significance

Abstract: Azelastine is a phthalazinone derivative with a wide spectrum of pharmacological activities. Actively sensitized guinea pigs were used to examine the broncholytic effect of azelastine in vivo. Furthermore, the influence of azelastine on the production of arachidonic acid (AA) metabolites was investigated in vitro and compared to the effects of nordihydroguaiaretic acid (NDGA), indomethacin and ketotifen. In vivo, azelastine protected actively sensitized guinea-pigs against ovalbumin-induced bronchospasm with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Support for this hypothesis comes from in vitro studies that bave shown that azelastine inhibits antigen-induced production of LTC4 and LTD4 by human and guinea pig lung fragments [10,24,35]. These studies suggest that azelastine achieves its effect by inhibiting the 5-lipoxygenase pathway of arachidonic acid metabolism in these cells [34]. If azelastine truly has 5-lipoxygenase inhibitory properties, then it might also be directly inhibiting that pathway of arachidonic acid metabolism in nasal mast cells without affecting the cyclo-oxygenase pathway or the process of degranulation and histamine release.…”
Section: Discussionmentioning
confidence: 98%
“…Support for this hypothesis comes from in vitro studies that bave shown that azelastine inhibits antigen-induced production of LTC4 and LTD4 by human and guinea pig lung fragments [10,24,35]. These studies suggest that azelastine achieves its effect by inhibiting the 5-lipoxygenase pathway of arachidonic acid metabolism in these cells [34]. If azelastine truly has 5-lipoxygenase inhibitory properties, then it might also be directly inhibiting that pathway of arachidonic acid metabolism in nasal mast cells without affecting the cyclo-oxygenase pathway or the process of degranulation and histamine release.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to, or as a consequence of their anti-histaminic activity, anti-histamines might also reduce the release of other mediators, including leukotrienes [23,24]. Azelastine shows many of these properties [25][26][27], among which decreased activation of mast cells coupled with decreased release of cysteinyl leukotrienes seems to be of particular relevance for the present study. Table 1 demonstrates that azelastine caused a two-fold reduction of the maximal response of FEV 1 during EAR, and montelukast an about four-fold reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Azelastine, a new phthalazinone derivative, is characterized by a long-lasting anti-allergic action and shows a broad spectrum of pharmacological activities promising for the treatment of bronchial asthma and allergic rhinitis [8]. It is a potent histamine HI-receptor antagonist which also inhibits the release of platelet activating factor and leukotrienes [8,9]. It has been suggested that the effect of azelastine may be mediated via suppression of radical generation and inhibition of calcium mobilization [10][11][12].…”
Section: Introductionmentioning
confidence: 99%